2017
DOI: 10.1111/jpc.13727
|View full text |Cite
|
Sign up to set email alerts
|

Conservative post‐natal management of antenatally diagnosed congenital pulmonary airway malformations

Abstract: Conservative management of CPAM may be considered for infants/children who remain asymptomatic, especially those with a small lesion. For large and medium-sized CPAM, delineation using computed tomography is required, and surgery may be beneficial to prevent late symptoms and the risk of emergency surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…The median age at resection was 6.7 months (interquartile range ¼ 3.6-11.4). 27 Style CC concluded that early elective resection of congenital lung malformations prior to 4 months of age is feasible and not associated with increased operative risk. 28 Most current studies have been conducted to determine the optimal timing for CPAM resection within the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…The median age at resection was 6.7 months (interquartile range ¼ 3.6-11.4). 27 Style CC concluded that early elective resection of congenital lung malformations prior to 4 months of age is feasible and not associated with increased operative risk. 28 Most current studies have been conducted to determine the optimal timing for CPAM resection within the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…In those with age, more than 6 months and mild to moderate symptoms, conservative management with closed observation is narrated. [13,14] We had lobectomy of all patients, as was indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment may be conservative or surgical. If an initial “wait and see” approach is adopted (13, 87), lung imaging may be repeated at 18 months of age, and if the CTM is confirmed, surgery should be planned around the 2nd birthday to allow the baby to grow (13). The rationale for this is to allow for possible spontaneous regression of the CTM, and thus a conservative approach is proposed until symptoms occur or when the cyst size changes on lung imaging (15, 16, 88, 89).…”
Section: Evidence On the Diagnostic Approach And Therapeutic Strategimentioning
confidence: 99%